1997
DOI: 10.1097/00005176-199701000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Prooxidant Effects of Maternal Smoking and Formula in Newborn Infants

Abstract: Exposure to maternal smoking in utero is prooxidant in newborn infants. Formula also has a prooxidant effect compared to colostrum in newborn infants not exposed to maternal smoking in utero. Further investigations will be necessary to explore the clinical consequences of these observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 28 publications
5
18
1
Order By: Relevance
“…Chelchowska et al (43) revealed that cigarette smoking increases lipid peroxidation and decreases antioxidant capacity in pregnant women and umbilical cord blood, as they found that endogenous free radical defence system enzyme activities such as CAT, GPx and glutathione reductase were decreased by 30 %, 15 % and 37 % in smoking pregnant women. In parallel to previous studies (8,44), our study indicates that smoking pregnant women and their newborns have a higher concentration of oxidative stress parameters.…”
Section: Discussionsupporting
confidence: 90%
“…Chelchowska et al (43) revealed that cigarette smoking increases lipid peroxidation and decreases antioxidant capacity in pregnant women and umbilical cord blood, as they found that endogenous free radical defence system enzyme activities such as CAT, GPx and glutathione reductase were decreased by 30 %, 15 % and 37 % in smoking pregnant women. In parallel to previous studies (8,44), our study indicates that smoking pregnant women and their newborns have a higher concentration of oxidative stress parameters.…”
Section: Discussionsupporting
confidence: 90%
“…Smoking mothers and their newborns had a higher concentration of oxidant status in previous studies [2,28]. However, we did not find any difference on MDA levels between smokers and non-smokers, in parallel to a previous study [13].…”
Section: Discussionsupporting
confidence: 82%
“…The nongenetic consequence of the hyperglycemic intrauterine environment gives credence to increase the diabetes-induced congenital malformations ( Hertogh et al, 2006 ). Human and animal studies have demonstrated that one of the most important mechanisms of action of diabetes is by ROS increased formation, and hence increased embryonic and fetal oxidative stress ( Ermis et al, 2004 ;Schwarz et al, 1997 ). Various etiological factors are proposed in order to explain diabetes-related congenital defects, especially at the early stages of organogenesis, they result in severe embryonic damage.…”
Section: Discussion ▼mentioning
confidence: 99%